Study of community-based waste management strategy determination in Magelang City - Ni Nyoman Nepi Marleni; Nurul Alvia Istiqomah; Bambang Agus Kironoto; Bambang Suhendro; Akhmad Aminullah; Danang Parikesit; Ahmad Rifa`i (Community Empowerment, 2022)
The city of Magelang is having trouble providing Final Disposal Sites (TPA), as the Banyuurip TPA's storage capacity has reached its limit and expansion is no longer possible. The only approach to reduce garbage production and residue transferred to landfills is to engage the community and all other stakeholders in waste management. This program intends to develop a waste management strategy in Magelang City starting with the smallest units, namely RT and RW. According to the findings, waste management solutions for the community of RW 02, Magelang Village, Central Magelang District may be classified as socialization strategies, work plans or regulations, resource procurement, cooperation, and empowerment. Furthermore, the study's findings reveal that an effective strategy must include multiple activities that operate concurrently, progressively, and sustainably, as well as the participation of various parties (community, local government, and universities) in assuring effective management implementation.